Stability Indicating HPTLC Method for Estimation of Tenofovir Disoproxil Fumarate in Bulk and Tablet Dosage Form (Asian Journal of Pharmaceutics (AJP), 2023)
Objective: A simple, precise, accurate, and rapid validated stability indicating high-performance thin-layerchromatography (HPTLC) method for estimation of Tenofovir Disproxil Fumerate was successfully developed.Materials and Methods: The method is based on HPTLC separation followed by densitometric measurementsof their spots at 266 nm. This method is based on HPTLC separation followed by UV detection at 266 nm.The separation was carried out on merckTLC aluminum sheets precoated with silica gel 60F254 using a camagLinomat 5. Results and Discussion: The mobile consists of Butanol:Ethyl acetate: Acetic acid (4.5:0.5:0.3 v/v).Calibration curves were linear in the range of 300–1800 ng/band,respectively Tenofovir disoproxil fumarate gavesharp and well-defined peaks at Rf value are 0.51, respectively,stress degradation study shows that sample degradedwith acid and base hydrolysis, under oxidation, thermal, and photolytic stress conditions. No chromatographicinterferences from the tablet excipients were found. The method was validated in accordance with the requirementsof International Conference on Harmonization guidelines Conclusion: Proposed method is precise, selective andaccurate for the estimation of tenofovir disoproxil fumarate in the bulk and dosage form.